Adversity Quotient Terhadap Fresh Graduate dalam Menghadapi Dunia Kerja : Literature Review - Kamila, Muna; Hidayah, Nurul; Aulia, Aulia (Faculty of Ushuluddin and Humanities, 2023)
Currently there is a lot of competition and competition in the world of work. The era of globalization is one of the causes for the development of science and technology to be very rapid, causing changes in the qualifications of higher demand for labor because it follows developments in the world of work and demands to be able to compete. This is a fear for everyone, especially fresh graduates. These conditions require the role of adversity quotient as an individual's ability to respond to obstacles and difficult situations so that fresh graduates can face various difficulties in facing the world of work. The purpose of this study is to conduct more in-depth research on the adversity quotient of fresh graduates in facing the world of work. The method used in this research is Literature review which is a scientific study that focuses on one particular topic. The keywords used to search for articles and journals are adversity quotient, fresh graduates, world of work and quantitative. The results obtained from this study are the influence of the adversity quotient on a person in facing the world of work, especially for fresh graduate. Keywords: Adversity Quotient, Fresh Graduate, World of Work